TECHNOGENIC FACTORS OF THE HYDROBIOLOGY REGIME OF THE VOLYNTSIVSKA RESERVOIR (UKRAINE) - Лялюк, Наталія (SWorldJournal, 2024)
The factors influencing the formation of the hydrobiological regime of the Volyntsyn Reservoir (Ukraine) were studied. The hydrochemical, sanitary and bacteriological parameters affecting phytoplankton under conditions of intensive operation of the reser